Sentinel lymph node biopsy in early-stage endometrium cancer using methylene blue dye - Govindan, Mannar Mannan; Srinivasan, Ayyappan; Pai, Ajit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The nodal evaluation of early-stage carcinoma endometrium has evolved rapidly, with various methods and dyes explored for sentinel lymph node biopsy (SLNB). Our study specifically aims to investigate the utilization of 1% methylene blue in SLNB for carcinoma endometrium at our center. Methods: In our prospective study of 105 patients with early-stage CA endometrium in our center between June 2021 and August 2022, we used 1% methyl blue dye for SLNB identification. We followed each patient for a minimum of 6 months. We documented demographic characteristics, SLNB features, and postoperative outcomes. Results: Out of 105 patients,94 patients (93%) of the study population belong to clinical FIGO stage IA disease.82 patients (81%) had biopsy specimens that showed endometrioid variant grade 1, followed by grade 2 in 13 patients (12.9%). 82 patients (81.2%) had unilateral SLNB visualisation 48 patients( 47.5%) had bilateral visualization of nodes. 19 patients (18.8%) of the study population had negative visualization of nodes on both sides. The average number of sentinel nodes retrieved was 2 nodes in 48 patients (45.5%), with a false negative rate of 4%. Conclusion: In our study, using a 1% methylene blue dye for an SLNB in Ca endometrium showed less than 50% success in visualizing both sides. Therefore, we do not recommend using it as a standard method. However, in resource-limited settings where indocyanine green (ICG) and radiocolloid are not available, considering methylene blue as an alternative is a viable option provided the SLNB algorithm is followed.